Delayed filling of the superficial middle cerebral vein in acute large artery occlusion - Xu, Jingsi; Zhang, Zheyu; Jin, Bo; Geng, Yu; Lin, Longting; Zhang, Sheng (Frontiers in Neurology, 2022)
Objective: The aim of this study was to determine whether the baseline delayed filling of the superficial middle cerebral vein (SMCV) is an independent cause of stroke prognosis in patients with acute anterior large vessel occlusion (LVO). Methods: Consecutive acute LVO (middle cerebral artery M1 ± intracranial internal carotid artery) patients between March 2019 and May 2020 were included. The delayed SMCV was defined as the delayed filling of SMCV in the affected side compared with the normal side throughout the venous phase on four-dimensional computed tomography angiography (4D-CTA) reconstructed from CT perfusion imaging. The modified Rankin scale (mRS) was used to evaluate the prognoses of these patients at 3 months after stroke. Results: In the total of 54 patients, 47 (87.0%) patients presented with baseline delayed SMCV, and 36 (76.6%) of these patients achieved SMCV reversal (ipsilateral delayed SMCV reversed to bilateral symmetrical SMCV) after reperfusion therapy. Successful reperfusion was independently associated with SMCV reversal (OR=69.328, 95%CI=2.818-175.342). A significant association between baseline SMCV delay and 3-month poor outcome (OR=19.623, 95%CI=1.567-245.727, P=0.021) was noted by multivariable regression analysis. Compared with patients with persistent delayed SMCV, patients with reversed SMCV did not show significant difference in the risk of 3-month poor outcome (OR=1.177, 95%CI=0.147-9.448). Conclusions: In acute LVO patients, baseline delayed SMCV was an independent cause of poor stroke prognosis, and the SMCV reversal cannot reverse the 3-month stroke prognosis. Therefore, the evaluation of baseline SMCV filling status should be strengthened in clinical practice.